Severe Thrombocytopenia Associated with Dengue Fever: An Evidence-Based Approach to Management of Thrombocytopenia. (12th August 2022) - Das, Sulagna; Abreu, Charles; Harris, Micah; Shrader, John; Sarvepalli, Satish
Abstract : Dengue is a mosquito-borne viral illness common in tropical and subtropical countries but very rare in the United States. Patients infected with dengue often present with thrombocytopenia. In the setting of dengue, platelet transfusions as a treatment for thrombocytopenia have no clear benefits in reduction of severe bleeding or improvement of the platelet count. Here, we present a case of a traveler infected with dengue virus and discuss the approach to treat thrombocytopenia.